Analysis on propagation law of shallow underground chemical explosion seismic waves - Wang, Liangquan; Kong, Deren (Frontiers in Physics, 2023)
Seismic waves generated by shallow underground explosions propagate differently from those generated by surface explosions. Thus, an accurate understanding of the propagation laws of seismic waves generated by explosions at various burial depths and TNT equivalent amounts is significant in assessing the destructive power of munitions and establishing guidelines for their application. In this study, we conducted several ground vibration velocity tests of shallow underground chemical explosion seismic waves for various TNT equivalent amounts and burial depths in a shooting range and analyzed the propagation of the seismic waves. Using the explosion similarity theory and dimensional analysis, we derived an equation for the estimation of the particle vibration velocity of shallow underground chemical explosion seismic waves. This equation calculation results have a very high degree of agreement with the measured data, measured data verify that the accuracy of the calculation model is better than 90.2%, which greatly improves the calculation accuracy of the shallow underground chemical explosion seismic wave particle vibration velocity, and thus provide effective theoretical support for analyzing explosion seismic waves in engineering tests.